Porewater-Derived Blue Carbon Outwelling and Greenhouse Gas Emissions in a Subtropical Multi-Species Saltmarsh - Zhu, Peiyuan; Chen, Xiaogang; Zhang, Yan; Zhang, Qianyu; Wu, Xuan; Zhao, Huawen; Qi, Liang; Shao, Xuexin; Li, Ling (Frontiers in Marine Science, 2022)
Saltmarshes can sequester atmospheric CO2 in sediments, but limited studies have quantified porewater-derived carbon exports and identified related carbon sources. Here, we estimated porewater exchange, carbon outwelling, and greenhouse gas emissions in a subtropical multi-species saltmarsh. The radon-based porewater exchange rate was estimated to be 5.60±2.78 cm d-1. As the most dominant ( 90%) carbon species, dissolved inorganic carbon (DIC) fluxes through porewater exchange and outwelling were 447±227 and 1200±61 mmol m-2 d-1, respectively, which were 1.2 and 3.2 times that of carbon burial. As most DIC can remain in the ocean for a long time, porewater-derived DIC outwelling represents another important carbon sink, in addition to carbon burial. CO2 and CH4 emissions from creek water were 54.6±0.5 and 0.19±0.01 mmol m-2 d-1, respectively, which could offset 16% of carbon burial. The δ13C and C/N ratios suggest that saltmarsh organic carbon mainly originates from the C3 plant Scirpus mariqueter rather than the C4 plant Spartina alterniflora. Overall, we demonstrate that porewater-derived DIC outwelling is an important long-term carbon sink in multi-species saltmarshes, providing a scientific basis for the protection and restoration of saltmarshes in the context of global climate change.